The effect of hatchery waste meal in ration on nutrient retention and performances of laying quails - Indreswari, R.; Ratriyanto, A. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of this study was to investigate the effect of hatchery waste meal (HWM) as a whole or without shell (shell-less) in the diet on nutrient retention and performance of quails. The study used 500 female quails (Coturnix coturnix japonica) aged 30 days with an average initial body weight of 94.75±4.17 gr. The quails were randomly allocated to five dietary treatments in a completely randomized design with 5 replicates of 20 quails. The dietary treatments were: Control = basal diet, Whole 4% = 96% basal diet + 4% whole HWM, Whole 8% = 92% basal diet + 8% whole HWM, Shell-less HWM 4% = 96% basal diet + 4% of shell-less HWM, Shell-less HWM 8% = 92% basal diet + 8% of shell-less HWM. The data were subjected to analysis of variance, when the treatments indicated significant effect it was continued with Duncan’s Multiple Range Test. Quails fed HWM up to 8% improved (P<0.05) their crude fat retention, apparent metabolizable energy, calcium consumption and calcium retention (P<0.05). In addition, HWM in the ration increased the performance, and also yolk and albumen weight, but decreased (P<0.05) yolk and albumen index. It can be concluded that HWM improved performance and nutrient retention of quails.